Mefloquine Inhibits Esophageal Squamous Cell Carcinoma Tumor Growth by Inducing Mitochondrial Autophagy - Xie, Yifei; Zhang, Jing; Lu, Bingbing; Bao, Zhuo; Zhao, Jimin; Lu, Xianyu; Wei, Yaxing; Yao, Ke; Jiang, Yanan; Yuan, Qiang; Zhang, Xiaofan; Li, Bo; et al. (Frontiers in Oncology, 2020)
Abstract Esophageal squamous cell carcinoma (ESCC) has a worldwide impact on human health, due to its high incidence and mortality. Therefore, identifying compounds to increase patients’ survival rate is urgently needed. Mefloquine (MQ) is a FDA-approved anti-malarial drug, which has been reported to inhibit cellular proliferation in several cancers. However, the anti-tumor activities of the drug have not yet been completely defined. In this study, mass spectrometry was employed to profile proteome changes in ESCC cells after MQ treatment. Sub-cellular localization and gene ontology term enrichment analysis suggested that MQ treatment mainly affect mitochondria. The KEGG pathway enrichment map of down-regulated pathways and Venn diagram indicated that all of the top five down regulated signaling pathways contain four key mitochondrial proteins (succinate dehydrogenase complex subunit C (SDHC), succinate dehydrogenase complex subunit D, mitochondrially encoded cytochrome c oxidase III and NADH: ubiquinone oxidoreductase subunit V3). Meanwhile, mitochondrial autophagy was observed in MQ-treated KYSE150 cells. More importantly, patient-derived xenograft mouse models of ESCC with SDHC high expression were more sensitive to MQ treatment than low SDHC-expressing xenografts. Taken together, mefloquine inhibits ESCC tumor growth by inducing mitochondrial autophagy and SDHC plays a vital role in MQ-induced anti-tumor effect on ESCC.